2000
DOI: 10.1016/s1097-2765(00)00033-2
|View full text |Cite
|
Sign up to set email alerts
|

A Yeast Intronic Splicing Enhancer and Nam8p Are Required for Mer1p-Activated Splicing

Abstract: Three introns whose splicing is activated during meiosis in S. cerevisiae contain a Mer1p-dependent splicing enhancer. The enhancer can impose Mer1p-activated splicing upon the constitutively spliced actin intron provided the basal splicing efficiency of actin is first reduced. Of several nonessential splicing factors tested, only the U1 snRNP protein Nam8p is indispensable for Mer1 p-activated splicing. We show that Mer1p associates with the U1 snRNP even in the absence of Nam8p or pre-mRNA. This work defines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 51 publications
4
90
1
1
Order By: Relevance
“…Unlike for the MER2 transcript, REC102 mRNA splicing efficiency was not affected by a mer1 mutation (Fig. 5c), as expected because the REC102 intron lacks a match to the consensus binding sequence for Mer1 (Spingola and Ares 2000). More surprising, however, splicing was frequently inaccurate, as ∼40% of the spliced message had a splice junction indicative of use of an alternative 3′ splice signal (UAG in the transcript) located 29 nucleotides upstream of the correct splice signal (Fig.…”
Section: Essential Sequence Encoded By a Previously Unrecognized 5′ Esupporting
confidence: 64%
See 1 more Smart Citation
“…Unlike for the MER2 transcript, REC102 mRNA splicing efficiency was not affected by a mer1 mutation (Fig. 5c), as expected because the REC102 intron lacks a match to the consensus binding sequence for Mer1 (Spingola and Ares 2000). More surprising, however, splicing was frequently inaccurate, as ∼40% of the spliced message had a splice junction indicative of use of an alternative 3′ splice signal (UAG in the transcript) located 29 nucleotides upstream of the correct splice signal (Fig.…”
Section: Essential Sequence Encoded By a Previously Unrecognized 5′ Esupporting
confidence: 64%
“…Mer2 (also known as Rec107) is also meiotically induced, but its expression is controlled differently. The MER2 message is constitutively expressed but contains an intron that is spliced efficiently only in the presence of a meiosis-specific splicing factor, Mer1 (Engebrecht et al 1991;Nandabalan and Roeder 1995;Spingola and Ares 2000). As a result of this regulation, Mer2 protein is present at low levels during vegetative growth and at substantially higher levels during meiosis (Henderson et al 2006;Li et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Antibody supershift assay+ Radiolabeled RNAs, wild-type 59 exon (lanes 1-4), L#456 (lanes 5-8), Up#6 (lanes 9-12), Up#2 (lanes 13-16), D#48 (lanes 17-20), and F1,F2-GT (lanes 20-24) were incubated with Kc nuclear extract for 30 min to allow complex assembly+ Affinity purified antibody was added after 30 min to the corresponding reactions as shown above each lane+ The free RNA (lanes 1, 5, 9, 13, 17, and 21) and RNA-protein complexes (A, B, and C) in the absence of antibody (lanes 2, 6, 10, 14, 18, and 22) are shown+ The supershifted complexes with anti- PSI (lanes 3, 7, 11, 15, 19, and 23) and anti-hrp48 (lanes 4, 8, 12, 16, 20, and 24) antibody are marked with arrows+ RNA-protein complex formed by PSI, hrp48, and several other unidentified proteins on the high affinity Up#6 SELEX RNA may inhibit splicing by sterically blocking U1 snRNP binding to the accurate 59 splice site and thereby preventing assembly of a functional spliceosome+ This idea of a steric block to U1 snRNP binding is consistent with previous results in which the F1/F2 sites were moved away from the IVS3 59 splice site resulting in a loss of inhibition (Siebel et al+, 1992)+ Because PSI can directly interact with U1 snRNP through its C-terminal A and B repeats, it is also possible that stably bound PSI protein on high affinity SELEX Up#6 RNA may bring U1 snRNP to the 59 exon RNA element in the absence of a strong U1 snRNA-pre-mRNA interaction and the presence of U1 snRNP and PSI would block the binding of U1 snRNP to the accurate 59 splice site+ Therefore, the presence of a strong PSI-binding site alone upstream of the IVS3 59 splice site appears to be sufficient to inhibit splicing of P element IVS3 in vitro+ There are several other reports of splicing factors that recruit U1 snRNP to the pre-mRNA and stabilize U1 snRNP-pre-mRNA interactions+ The yeast RNAbinding protein Mer1p, which has a single KH domain, is involved in mediating meiosis-specific alternative splicing of the MER2 pre-mRNA (Engebrecht et al+, 1991)+ Mer1p, which is expressed only in meiosis, binds to the region downstream of the weak 59 splice site of the MER2 transcript to facilitate meiosis-specific splicing of this intron+ Mer1p associates with U1 snRNP in the absence of MER2 target RNA (Spingola & Ares, 2000)+ By dividing the Mer1p protein into two fragments containing either the C-terminal KH domain or the N-terminal domain, it is known that only the N-terminal domain can coimmunoprecipitate U1 snRNA and that the KH domain has no direct interaction with U1 snRNP (Spingola & Ares, 2000)+ The yeast U1 snRNP-specific protein Nam8p, which is stably associated with U1 snRNA, has been shown to be required for efficient recognition of weak 59 splice sites (Puig et al+, 1999)+ It has been shown that Nam8p also binds to the region downstream of the weak 59 splice site of MER2 pre-mRNA and stabilizes the U1 snRNA-pre-mRNA base pairing interaction (Puig et al+, 1999)+ The mammalian homolog of Nam8p, the TIA-1 protein that was first identified as an effector of apoptosis (Tian et al+, 1991), also has been shown to function in U1 snRNP recruitment to a weak 59 splice site in the human apoptosis signaling receptor gene Fas premRNA (Forch et al+, 2000)+ TIA-1 interacts with the region downstream of the weak 59 splice site in the fas gene intron 5 to promote splicing and inclusion of the downstream exon 6 yields an mRNA encoding a membrane-bound active form of the fas receptor+ Another example of potential U1 snRNP...…”
Section: Discussionmentioning
confidence: 99%
“…The YRA1 intron is unusual in size, location within the coding region, and in the sequence of one of the consensus splicing signals (Portman et al+, 1997 (2002) was that cells expressing YRA1 containing the RPL25 intron from the YRA1 promoter had a slight dominantnegative growth defect at 37 8C+ Intriguingly, some of the introns we have tested, notably that of ACT1, could partially complement the growth defect of YRA1-⌬IVS+ It thus seems that the YRA1 intron shares some characteristics that are relevant for autoregulation with a subset of introns from unrelated yeast genes+ These observations will likely facilitate the identification of cisacting regulatory elements in the YRA1 transcript+ For example, like the YRA1 intron, the RPL25 and ACT1 introns are unusually large (414 and 408 nt, respectively), whereas both the UBC8 and YRA1 introns have branchpoint sequences that differ from the normally highly conserved consensus at the first position (CAC UAAC and GACUAAC, respectively)+ In addition, the discrepancies between our findings and those of Rodriguez-Navarro et al+ (2002) might, at least in part, also reflect subtle differences in the experimental details involved, such as different strain backgrounds or plasmid-copy numbers+ Even though we do not know at this point which of the peculiarities of the YRA1 intron mentioned above are involved in autoregulation, each of these characteristics has been shown to be important in the few reports of regulated splicing in yeast+ One prominent example is the meiosis-specific splicing of MER2 premRNA+ During mitotic growth, basal splicing efficiency is lowered by a noncanonical 59 splice site and an unusually large 59 exon (Engebrecht et al+, 1991;Nandabalan & Roeder, 1995)+ Activation of splicing during meiosis requires a splicing enhancer located downstream of the 59 splice site (Spingola & Ares, 2000) and the product of the MER1 gene that is only expressed during meiosis and specifically binds to the MER2 splicing enhancer (Nandabalan & Roeder, 1995;Spingola & Ares, 2000)+ Another well-studied example is the ribosomal protein L30, which regulates splicing of the transcript of its own gene, RPL30+ Binding of L30 to an RNA structure formed by nucleotides surrounding the noncanonical 59 splice site of RPL30 inhibits splicing prior to the first step (Eng & Warner, 1991;Vilardell & Warner, 1994)+ Finally, autoregulation of DBP2, a member of the DEAD-box family of putative RNA helicases, depends on the presence of a 1,002-nt intron, the largest in S. cerevisiae (Barta & Iggo, 1995)+ To our knowledge, YRA1 is the first example of a yeast gene that causes a dramatic growth defect when its intron is removed+ No effect on growth has been observed as a result of DBP2 overexpression from a cDNA copy (Barta & Iggo, 1995)+ Moreover, a cocultivation assay capable of revealing subtle differences in biological fitness was required to show that mutations in RPL30 that abolish autoregulation lead to detectably slower growth only over the course of many generations (Li et al+, 1996)+…”
Section: Expression Of Yra1p Is Regulated On the Level Of Splicingmentioning
confidence: 99%